2006
DOI: 10.1080/09637480600858134
|View full text |Cite
|
Sign up to set email alerts
|

Can pure fruit and vegetable juices protect against cancer and cardiovascular disease too? A review of the evidence

Abstract: While it is widely accepted that fruit and vegetables (F&V) lower the risk of cancer, and cardiovascular disease (CVD), the role of pure fruit and vegetable (PFV) juices is often downplayed. This review poses two questions: Are the protective benefits of F&V dependent upon constituents lacking in PFV juices (e.g. fibre)? Do PFV juices impact on disease risk when considered separately from F&V? Studies comparing the effects of fibre and antioxidants were reviewed, yielding the finding that the impact of F&V may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 80 publications
0
80
2
11
Order By: Relevance
“…This is controversial because most reviews link sugar sweetened beverages consumption with greater risk of obesity and metabolic syndrome (6,38). In this sense, it is important to say that, in our study, water from all types of liquids that provide calories, including dairy products and fruit juices, were the drinks most consumed by our children (39), which could justify our results, as some authors present a possible positive relationship with body composition and cardiovascular health (12,40).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…This is controversial because most reviews link sugar sweetened beverages consumption with greater risk of obesity and metabolic syndrome (6,38). In this sense, it is important to say that, in our study, water from all types of liquids that provide calories, including dairy products and fruit juices, were the drinks most consumed by our children (39), which could justify our results, as some authors present a possible positive relationship with body composition and cardiovascular health (12,40).…”
Section: Discussioncontrasting
confidence: 40%
“…Most studies have focused on sugar sweetened beverages consumption (4-7), although there are also studies that analyzed diet beverages (8,9). On the other hand, there are studies focused on dairy consumption and its possible positive association with cardiovascular health (10,11), as well as on natural juices intake (12). Preliminary analysis of a recent study has shown that a Healthy Beverage Index, a measure of the overall healthfulness of an individual's beverage intake, was associated with reduced cardiometabolic risk in adults (13).…”
Section: Introductionmentioning
confidence: 99%
“…Pure fruit and vegetable juice offer similar health benefit as having whole fruits and vegetables [Ruxton et al, 2006] . Undoubtedly, their content of antioxidants, polyphenol and fibres are good for health.…”
Section: Discussionmentioning
confidence: 98%
“…The value of antioxidants in food has long been recognized for their health benefits. It is believed that higher intake of antioxidant rich fruits are associated with decreased risk of degenerative diseases particularly coronary heart disease (CHD) and cancer (Ruxton et al 2006). The beneficial effect of fruits is mainly associated with the radical scavenging activity of polyphenols, which are largely present in fresh fruits and their processed products.…”
Section: Introductionmentioning
confidence: 99%